2021
DOI: 10.3390/electronics10070785
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Vehicular Ad-Hoc Network Computing Using Deep Neural Network with IoT-Based Bat Agents for Traffic Management

Abstract: In this paper, Deep Neural Networks (DNN) with Bat Algorithms (BA) offer a dynamic form of traffic control in Vehicular Adhoc Networks (VANETs). The former is used to route vehicles across highly congested paths to enhance efficiency, with a lower average latency. The latter is combined with the Internet of Things (IoT) and it moves across the VANETs to analyze the traffic congestion status between the network nodes. The experimental analysis tests the effectiveness of DNN-IoT-BA in various machine or deep lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 80 publications
1
29
0
Order By: Relevance
“…In several studies, the aim was to provide composite services through integration into wireless sensor networks (WSNs) [17][18][19][20][21]. A three-third party service-oriented architecture is suggested by Zhou et al [4]. As a service in a service class, the work of each sensor is abstracted.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, the aim was to provide composite services through integration into wireless sensor networks (WSNs) [17][18][19][20][21]. A three-third party service-oriented architecture is suggested by Zhou et al [4]. As a service in a service class, the work of each sensor is abstracted.…”
Section: Related Workmentioning
confidence: 99%
“…In general, intelligent objects, since they are battery operated devices, wireless sensors and cell phones, have very little resources for calculation and storage. With the advent and speed of service-defined creation, intelligent objects are seen as services that match their cohosted functions [4][5][6]. In other words, a standard service can be used directly to provide each IoT smart entity with a feature.…”
Section: Introductionmentioning
confidence: 99%
“…in particular In addition, the REPC, a current transmission device, collects and reveals additional information about the energy level in the nodes, which makes for a more efficient distribution of network resources. This research done by [8] authors compared routing protocols and IoT Medium Access Control (MAC), and their conclusions indicated that existing protocols do not provide for cooperation between routing strata and MAC layers; new requirements were therefore proposed as a consequence of this discovery. These requirements enable routing protocols to perform necessary modifications, such as to the MA and routing protocols, while also allowing adjustment of the parameters as needed.…”
Section: Related Workmentioning
confidence: 99%
“…In some cases, ANN are combined with some other methods to increase efficiency of the hybridized model. For example, deep neural networks are hybridized with bat algorithm (BA) to provide a dynamic form of traffic control in vehicular ad-hoc networks (Kannan et al, 2021). The proposed model has shown precise traffic flow predictions in real-time conditions and, as a result, the main traffic parameters are improved, including decrease in delay, fuel consumption, and emissions.…”
Section: Neural Network and Traffic Management Systemsmentioning
confidence: 99%